2015
DOI: 10.1159/000441437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a More Permeable Dialysis Membrane on ESA Resistance in Hemodialysis Patients - A Pilot Investigation

Abstract: Background/Aims: Hemodialysis (HD) patients often show impaired response to erythropoiesis-stimulating agents (ESAs). Extended HD membrane permeability may potentially improve ESA response. Methods: Twenty-four prevalent HD patients were randomly assigned to 12 weeks use of high cut-off (HCO) membrane (in every second dialysis treatment) or continued treatment with high-flux membrane. We monitored changes in hemoglobin (Hb), ESA dose, and key biochemical markers. Results: The Hb level increased in the study gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Also Stefansson et al [34], in a short-term study consisting of a small population of 20 patients, suggested that hepcidin levels were significantly reduced after 60 days of high volume OL-HDF with respect to low-flux HD. The role of membrane permeability in removing high quantity of hepcidin and in reducing its pre-HD levels has been confirmed by Teatini et al [35] using a high cut-off membrane. In the study group, 50% reduction on hepcidin level was achieved and it was associated with an increase of hemoglobin level.…”
Section: Current Strategies To Improve Esa Hyporesponsivenessmentioning
confidence: 83%
“…Also Stefansson et al [34], in a short-term study consisting of a small population of 20 patients, suggested that hepcidin levels were significantly reduced after 60 days of high volume OL-HDF with respect to low-flux HD. The role of membrane permeability in removing high quantity of hepcidin and in reducing its pre-HD levels has been confirmed by Teatini et al [35] using a high cut-off membrane. In the study group, 50% reduction on hepcidin level was achieved and it was associated with an increase of hemoglobin level.…”
Section: Current Strategies To Improve Esa Hyporesponsivenessmentioning
confidence: 83%
“…Most recently, an innovation called expanded hemodialysis (HDx), which uses an MCO membrane that allows for improved removal of molecules with a size of 25 kDa and above, including larger uremic toxins. Furthermore, expanded hemodialysis can be used with the same process and personnel as HD, which means that it can be implemented with relatively low costs, and early clinical evidence suggests that using HDx has the potential to improve patient outcomes and quality of life [ 11 , 12 ]. However, evidence of the potential economic value of using of HDx remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Using high volume OL-HDF, Stefansson et al obtained a significant (38%) reduction of serum hepcidin levels after 60 days of treatment (34). In turn, in the Teatini et al study, the use of high cutoff membrane confirmed the removal of a high quantity of hepcidin and a 50% reduction its pre-dialysis serum level (35). The application of convective transport and good membrane permeability appears to be the solution to obtain lower levels of hepcidin in dialysis patients; however, it should be confirmed in future large-scale studies.…”
Section: Hepcidin In Chronic Kidney Diseasementioning
confidence: 93%